Increases in Serum Nitrite and Nitrate of a Few-Fold Adversely Affect the Outcome of Pregnancy in Rats - Tsuneo Inoue; Muneshige Kaibara; Yasuko Sakurai-Yamashita; Masahiro Kawano; Tadayuki Ishimaru; Kohtaro Taniyama (Elsevier, 2004)
The objective of this study was to evaluate serum nitrite and nitrate (nitrite/nitrate) concentrations that affect adversely pregnancy outcome. Pregnant rats, from day 2 to day 8 of pregnancy, were daily given subcutaneously several doses (5, 10, and 30 mg/rat) of diethylenetriamine-nitric oxide (DETA/NO). Serum nitrite/nitrate concentrations were measured using an HPLC system. Serum nitrite/nitrate concentrations increased dose-dependently with DETA/NO. Effects of DETA/NO on pregnancy outcome were assessed on day 14 of pregnancy. In rats given 5 mg DETA/NO, there was a significant increase in serum nitrite/nitrate concentrations (49.2 vs 24.6 μmol/l, P<0.001), and both placental weight and fetal weight decreased compared to control rats. Macroscopic bleeding in placenta was frequently observed in rats given DETA/NO. We further studied effects of DETA/NO on cultured trophoblastic BeWo cells. DETA/NO added to the culture medium increased nitrite/nitrate concentrations in the medium in a dose-dependent manner. Nitrite/nitrate concentrations in the medium over four times the concentration of control decreased progesterone in the medium at 24 h after the application of DETA/NO. The hormonal secretion was not affected by DETA only. This study shows for the first time nitrite/nitrate concentrations affecting adversely pregnancy outcome and function of the trophoblastic cells. Keywords:: nitric oxide (NO), pregnancy, HPLC, diethylenetriamine-NO